Aplasia cutis congenita associated with coarctation of the aorta. Case report and review of the literature. - Silva-Díaz, E.; Guillen-Climent, S.; Estebánez, A.; Saéz-Martín, L.; Martín, J.M. (European Journal of Pediatric Dermatology, 2020)
The presence of aplasia cutis congenita (ACC) in a newborn may be indicative of cardiovascular malformations (CVM), especially in those cases where there is a family history of ACC, terminal limbs defects and/or CVM. We reported the case of a two-month-old baby girl with scalp ACC associated with coarctation of the aorta and other CVM. A literature review was also made.